The Role of Pharmacists in General Practice in Asthma Management: A Pilot Study - Louise S. Deeks; Sam Kosari; Katja Boom; Gregory M. Peterson; Aaron Maina; Ravi Sharma; Mark Naunton (MDPI AG, 2018)
Background: Asthma is principally managed in general practice. Appropriate prescribing and medication use are essential, so general practice pharmacists appear suitable to conduct asthma management consultations. This pilot study aimed to evaluate the asthma management role of a pharmacist in general practice. Methods: Analysis of an activity diary and stakeholder interviews were conducted to identify interventions in asthma management; determine whether asthma control changed following pharmacist input; and determine acceptability of asthma management review by a pharmacist in one general practice in Canberra, Australia. Results: Over 13 months, the pharmacist saw 136 individual patients. The most common activities were asthma control assessment; recommendations to adjust medication or device; counselling on correct device use; asthma action plan development and trigger avoidance. For patients with multiple consultations, the mean Asthma Control Test score improved from the initial to last visit (14.4 ± 5.2 vs. 19.3 ± 4.7, n = 23, p < 0.0001). Eight of the 19 (42%) patients moved from having poor to well-controlled asthma. Case studies and qualitative data indicated probable hospital admission avoidance and stakeholder acceptability of asthma management by a practice pharmacist. Conclusions: This pilot study demonstrated it is feasible, acceptable and potentially beneficial to have a general practice pharmacist involved in asthma management. Fuller evaluation is warranted.